Design and analysis of refrigerator cooling load for fruit and vegetable storage in tropical climate - Kahfi Alwi Kasim; Boni Sena; Oleh; M. Keitaro Ramadhan; Alwi Azwar Anas; Angga Muhamad Najib (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
This study proposes a domestic refrigerator design based on Phase Change Material (PCM) integration to improve fruit and vegetable storage performance in tropical climates with high temperature and humidity. The study was conducted in two representative conditions, namely Karawang (high temperature) and Banjarmasin (high humidity). The methodology includes thermodynamic-based cooling load analysis (transmission, product, and infiltration load), the use of BMKG climatology data, and three-dimensional geometric modeling using SolidWorks. A 15 mm thick RT4/RT5 PCM was integrated into the cabinet wall as a thermal buffer to reduce temperature fluctuations. The results show that the total cooling load is 103.58 W (Karawang) and 102.42 W (Banjarmasin), respectively, with transmission load dominating at high temperature conditions and a 7.5% increase in latent infiltration load at high humidity conditions. The system is then designed using a 1/8 HP compressor with R134a refrigerant, resulting in a theoretical COP of 3.59. The key findings demonstrate that the integration of PCM into a hybrid wall structure is effective in stabilizing internal temperatures and improving the system's resilience to variations in environmental thermal loads. This approach provides a relevant design contribution to the development of domestic refrigerators in extreme tropical regions